Employee Benefits as a Moderator of Work Conditions and Performance - Widiastini, Putri; Gorda, Anak Agung Ngurah Oka Suryadinatha (Jurnal Minds: Manajemen Ide dan Inspirasi, 2025)
This study analyzes the effects of work-life balance, working atmosphere, mental health, supervisor leadership, peer support, and job satisfaction on work performance, with employee benefits as a moderating variable among banking employees. Using a quantitative approach and PLS-SEM on 291 respondents, the results show that working atmosphere, mental health, supervisor leadership, peer support, and job satisfaction significantly improve work performance, while work-life balance has no significant direct effect. Employee benefits do not directly affect performance but significantly strengthen all relationships. The findings emphasize the importance of supportive work environments and employee benefits in enhancing performance.